Enantioselective toxicity and degradation of chiral herbicide fenoxaprop-ethyl in earthworm Eisenia fetida. (April 2017) - Jing, Xu; Yao, Guojun; Liu, Donghui; Qu, Han; Zhou, Qian; Zhou, Zhiqiang; Wang, Peng
Graphical abstract: Highlights: Acute toxicity of fenoxaprop-ethyl and its four metabolites was conducted. Enantioselective toxicity of fenoxaprop-ethyl and its chiral metabolites was found. Enantioselective degradation of fenoxaprop-ethyl in earthworms was investigated. Abstract: The enantioselective degradation of fenoxaprop-ethyl in ecological indicator earthworm was studied and the main metabolites (fenoxaprop, 6-chloro-2, 3-dihydrobenzoxazol-2-one, ethyl-2-(4-hydroxyphenoxy)propanoate, 2-(4-hydroxyphenoxy)propanoic acid) were also monitored on an enantiomeric level. The individual enantiomers of fenoxaprop-ethyl and its three chiral metabolites were prepared to study the acute toxicity to earthworm. Chiral analysis methods were set up based on HPLC–MS/MS with chiralpak IC chiral column. Fenoxaprop-ethyl was not found in earthworms, while the primary metabolite fenoxaprop was in relatively high levels indicating a quick hydrolysis degradation. Fenoxaprop was accumulated almost exclusively with R-enantiomer in earthworms and the bio-concentration factors of R-fenoxaprop and S-fenoxaprop were 1.39 and 0.17 respectively with the enantiomer fraction (EF) values about 0.99. The degradation of R-fenoxaprop in earthworms followed first-order kinetics with half-life of 1.82 day. The other metabolites could not be detected in earthworms. The calculated LC50 values showed ecological indicator earthworm was more sensitive to the four metabolites than fenoxaprop-ethyl. Furthermore, earthworm was more sensitive to the R-form of the chiral metabolites than the S-form and rac-form. The results suggested metabolites and enantioselectivity should be taken into consideration to better predict the exposure concentration and apply ecological indicators in toxicological studies.